Agência e complexidade: uma análise dos fundos brasileiros de investimento em ações - Sergio Louro Borges (2018)
In situations in which the separation between the owners and managers takes place, the informational asymmetry appears, being able to generate the problem known as agency conflict. Among the possible agency conflicts, indications of investment allocation with the focus on the increase of the fees charged or increased visibility of the funds at specific moments have already been detected in the national literature. In addition, international studies point to the use of the complexity of financial assets as a source of information asymmetry, reducing the profitability of investments for the benefit of managers and issuers of these securities. However, there is still a theoretical gap regarding the impacts of portfolio allocations for different groups of investment fund investors. In order to fill this gap, the objective of this thesis was to identify the conflicts of interest and the impacts of complexity in the Brazilian investment funds market through the study of the allocation of their investments. To this end, the selected funds were grouped according to their target audience and charged rates, forming portfolios with medium characteristics. The analyzes were divided into three stages, of which the first looked for indications of the problem of quota inflation and possible assets used to do so. The second stage proposed the Portfolio Complexity Index (ICC), which allows the measurement of the complexity of the investments, respecting the individual complexities of the different types of assets and their holdings in the portfolios. In the last stage of the analysis, the ICC was used as a proxy for the complexity of the portfolios in order to verify their changes in specific moments and their impact on risk and the return of funds. The results indicate a greater use of complexity by the groups of funds whose target audience was the unqualified investors, being consistent with results presented in the current literature. Another result consistent with recent studies was the greater evidence of quota inflation in the period immediately following the change in the legislation regarding the calculation of the profitability of the funds, which occurred as of CVM Instruction 465 of 2008. In addition, that funds that do not charge fees, regardless of target audience, are hampered by the use of the complexity of the investment portfolio, with the increased risk assumed.